Delivering Method And Functioning Of Al-Khabar In Two-Way Arabic Dialogue: Case Study Verses Of Quran - Abd Latif, Mohd Abdul Nasir; Ismail, Zawawi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study is about the al-Khabar language register found in the verses of the two-way dialogue in the Qur'an. The dialogue applies question-answer between two parties. Al-Khabar is a speech that has the probability of authenticity or falsity. This study explores the delivery method of al-khabar by the Qur'an dialogue process and analyzes its functionality. The analysis is carried out using a qualitative approach using the theory of al-Jurjani (1994), al-Hashimi (1994), and al-Samarra'i (2000) as the basic framework of analysis. The findings show that not all bilateral dialogues in the Qur'an begin with the first level and end with the third level. There is a dialogue that only uses ibtida level, level of talibi and inkari, and level of ibtida', talibi dan inkari. The findings also show that the nominal sentence or jumlah ismiyyah is used in verses in the form of Divine recognition. In contrast, the jumlah ismiyyah and jumlah fi'liyyah are used in attitude, behavior, and actions. For underscoring eternity, the al-Khabar register also uses the al-Shart wa al-Jawab language style.